1997
DOI: 10.1007/bf00879663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on the cerebral distribution of technetium-99m hexamethylpropylene amine oxime in healthy humans

Abstract: Some brain functions decline at a linear rate throughout adulthood. Others remain relatively stable until very late in the life cycle. This study characterized the effects of aging on the regional cerebral distribution of hexamethylpropylene amine oxime (HMPAO) in healthy human volunteers. The sample consisted of 26 men and 18 women with a mean age of 41.6+/-14.9 years (range: 19-73). Their past medical histories, physical examinations, and laboratory screening tests were normal. Single-photon emission tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A comparison of mean baseline oxyHb levels by age found levels to be significantly lower for the older adults in eight channels, as supported by studies suggesting that cerebral blood flow declines with age in the gray matter (Mozley et al, 1997), the regions of the inferior frontal gyrus, both sides of the middle frontal gyrus, the left superior temporal gyrus, both sides of the cingulate gyrus (Takahashi et al, 2005), the parietal region, the left frontotemporal cortex, and the temporal cortex (Pagani et al, 2002). Although Takahashi et al (2011) suggested that in the frontal region, blood flow in the scalp accounts for most NIRS signals, even our study found that from the parietal to the frontal region, there was a significant age-related decline in blood flow.…”
Section: Discussionmentioning
confidence: 64%
“…A comparison of mean baseline oxyHb levels by age found levels to be significantly lower for the older adults in eight channels, as supported by studies suggesting that cerebral blood flow declines with age in the gray matter (Mozley et al, 1997), the regions of the inferior frontal gyrus, both sides of the middle frontal gyrus, the left superior temporal gyrus, both sides of the cingulate gyrus (Takahashi et al, 2005), the parietal region, the left frontotemporal cortex, and the temporal cortex (Pagani et al, 2002). Although Takahashi et al (2011) suggested that in the frontal region, blood flow in the scalp accounts for most NIRS signals, even our study found that from the parietal to the frontal region, there was a significant age-related decline in blood flow.…”
Section: Discussionmentioning
confidence: 64%
“…Age-related and regionally specific decreases in resting cerebral glucose metabolism and similar age-related declines in CBF and oxygen consumption have been reported in many articles in which modern, highresolution PET scanners were used. [12][13][14][15][16][17][18][19][20][21][22][23] Consistently, the slope of the metabolic decline relative to the age and the degree of difference in metabolism between young and older people varied according to the regions examined. For example, in a recent study in which the effects of healthy aging on the regional cerebral glucose metabolism were assessed with SPM, 23 the bilateral and symmet- rically distributed effects of age were most marked in the inferior and posterior lateral frontal, anterior cingulate, perisylvian temporoparietal and anterior temporal cortices, left caudate head, and anterior thalamus.…”
Section: Discussionmentioning
confidence: 97%
“…9 However, proper assessment of elderly patients with neurodegenerative diseases, such as Alzheimer's disease, requires knowledge about the effects of aging. There have been many reports showing age-and/or gender-related effects on the regional CBF, [12][13][14] glucose metabolism, [15][16][17][18][19][20][21][22][23] and several neuroreceptor systems. [24][25][26] Usually, those effects are regionally specific.…”
mentioning
confidence: 99%
“…The reason that we only found weak age-related changes can be that our study group was older than in these studies. Mozley et al (1997) showed that most of age-related changes occur during young adulthood. They found that the rate of change became negligible after 36 years of age, i.e.…”
Section: Discussionmentioning
confidence: 99%